2013
DOI: 10.1371/journal.pone.0069780
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ultrasound Induced Inertial Cavitation to Non-Invasively Restore Coronary and Microvascular Flow in Acute Myocardial Infarction

Abstract: Ultrasound induced cavitation has been explored as a method of dissolving intravascular and microvascular thrombi in acute myocardial infarction. The purpose of this study was to determine the type of cavitation required for success, and whether longer pulse duration therapeutic impulses (sustaining the duration of cavitation) could restore both microvascular and epicardial flow with this technique. Accordingly, in 36 hyperlipidemic atherosclerotic pigs, thrombotic occlusions were induced in the mid-left anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
(36 reference statements)
3
27
0
4
Order By: Relevance
“…Sutton et al (2013b) extended this model, and showed that increased thrombolysis occurred only in unretracted clots. Xie et al (2013) noted that epicardial recanalization was greatest in a porcine atherosclerotic model when Doppler pulses induced cavitation activity from Definity ® in the presence of rt-PA.…”
Section: 3 Experimental Evidence For Ultrasound-enhanced Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Sutton et al (2013b) extended this model, and showed that increased thrombolysis occurred only in unretracted clots. Xie et al (2013) noted that epicardial recanalization was greatest in a porcine atherosclerotic model when Doppler pulses induced cavitation activity from Definity ® in the presence of rt-PA.…”
Section: 3 Experimental Evidence For Ultrasound-enhanced Efficacymentioning
confidence: 99%
“…Ultrasound is well established to enhance thrombolysis in-vitro (Datta et al 2006; Prokop et al 2007), ex-vivo (Hitchcock et al 2011), and in-vivo (Culp 2004; Xie et al 2013). Mechanical effects, particularly acoustic cavitation (Petit et al 2012a; Wu et al 2014; Bader et al 2015), are clearly responsible for enhanced thrombolysis.…”
Section: 3 Experimental Evidence For Ultrasound-enhanced Efficacymentioning
confidence: 99%
“…These cavitational responses can be elicited from commercially available microbubbles when insonified with diagnostic ultrasound frequencies and mechanical indices (Xie et al 2009a). However, diagnostic ultrasound pulse durations are very short, and all previous work with diagnostic ultrasound transducer frequencies to enhance thrombus dissolution have been in the presence of TPA with or without microbubbles (Laing et al 2012; Ricci et al 2012; Basta et al 2004; Xie et al 2013). There is no data on the use of diagnostic ultrasound and microbubbles alone (without a fibrinolytic agent) to dissolve thrombi.…”
Section: Introductionmentioning
confidence: 99%
“…Even at these sizes though, they would still be expected to pass freely through the myocardial capillaries (13) while also being more resistant to destruction than smaller sized perfluorocarbon microbubbles (14). Intravenously infused commercially available microbubbles within the capillaries would not be visualized at this high mechanical index and frame rate, since capillary blood replenishment with intravenously infused C3 microbubbles would not be expected at this frame speed (10). It is possible, therefore, that these created microbubbles were in a unique size range that was resistant to ultrasound induced destruction but still capable of acting as free intravascular tracers.…”
Section: Discussionmentioning
confidence: 99%
“…One additional pig without infarction was utilized to demonstrate the effect of mechanical index on activation threshold in real time and the wash out of activated droplets from the myocardium and left ventricular cavity. The infarction was created using an established protocol (10,11) that involves balloon injury of the mid left anterior descending artery followed by a 50 day 15% lard diet. At 50 days, the left anterior descending was balloon-injured again in the same location, following which the balloon was reinflated slightly proximal to the injury site to create stasis, and small 0.2–0.3 milliliter aliquots of thrombosing venous blood were re-injected through the balloon catheter until a sustained (20 minute) angiographic occlusion was achieved.…”
Section: Methodsmentioning
confidence: 99%